(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The rapid development of industry increases the demand and importance of chromium. In this study, beneficiation possibilities of the representative chromite ore taken from the Tokat Province with a laboratory type jig, spiral concentrator, shaking table and multi gravity separator (MGS) were investigated. Appropriate particle size fractions were fed into each beneficiation device. Experimental studies were shown as a flow chart. The shaking table gave the best results for chromite beneficiation and a concentrate of 47.02% Cr2O3 grade and 94.29% recovery were obtained by using a -0.3+0.106 mm particle size fraction. It was observed that concentrates with saleable grade could be obtained as a result of the beneficiation of chromite ore with a spiral concentrator. The tailings obtained from the jig, spiral concentrator and shaking table were blended and scavenger experiments were carried out with an MGS to recover the remaining chromite in the tailings. 93.55% of the chromite in this blended sample was recovered with a grade of 34.96% Cr2O3. Hence, MGS seems to be the promising equipment for the beneficiation of tailings.